(untitled) (Eurasian Medical Research Periodical, 2021)
Impacted teeth could be defined as UN succeeded tooth eruption at its proper position. Mostly impacted teeth are wisdom, and after followed by upper canine and lower premolar. During and after removal of the impacted teeth, some complications may be seen such as damage to adjacent teeth. Conventional radiograph in dentistry such as periapical, cephalometric and panoramic radiographs (OPG) provide only (2D) examination. Thus, they provide limited information about the anatomical structures, size, and localization of any incidental lesions. Also, there are many disadvantages of (2D) imaging methods such as cross-bite, magnification, and distortion of images. Due to insufficiency of (2D) imaging methods, a novel method named cone-beam computed tomography (CBCT) which is specially developed to use in head and neck imaging. CBCT has several benefits including low radiation dose, accurate precise evaluation, faster scan, lesser artifact, and magnification. In our study, we attempt to detect many incidental finding in the maxillofacial region during pre-evaluation of impacted teeth (that they have indications of surgical removal) by OPG or CBCT images of 70 patients were assessed and resulting data were compared. We want to conclude that when examing the patient by any investigating tool for finding of the exact cause of any problem that encounters them, we get early diagnosis of many diseases or problems and it will result of easy and early treatment of them, also we can say that CBCT imaging is obligation not a choice in today’s technology